PENGARUH SIZE, PROFITABILITY, LEVERAGE, KOMITE AUDIT DAN INTENSITAS PERSEDIAAN TERHADAP EFFECTIVE TAX RATE (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar dalam BEI 2015-2017) - Dewi Purnamasari, 15.05.52.0214; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2019)
This study was conducted to examine the effect of the size, profitability, leverage, audit committee and inventory intensity, the object of research used by manufacturing companies listed on the Indonesia stock exchange for the period 2015-2017 The number of selected samples is 161 observations determined using purposive sampling method. Data collection was done by documentation technique collected through IDX website and BEI Corner-Unisbank Stikubank (Unisbank).Analytical technique used is multiple regression. The results of the analysis show that profitability, leverag and audit committe are able to influence effective tax rate, while size and audit committee are not able to influence effective tax rate.